PROSPECTS FOR STRENGTHENING THE INTEGRATION OF SCIENCE AND PRODUCTION IN HIGHER EDUCATIONAL INSTITUTIONS OF UZBEKISTAN - Bakhtiyor Khajiev (Modern American Journals, 2025)
This article is devoted to strengthening integrational relations between science and production in higher educational institutions. In the modern world, where innovations and technological changes occur at high speed, the need for effective interaction between the academic and industrial spheres becomes especially relevant.
Keywords: Science, production, integration, clustering, interviews.